تقييم اداء الشبابيك الاسلامية في البنوك العمومية الجزائرية دراسة حالة البنك الوطني الجزائري - وكالة بريكة - - أحمد نيد; بلال بن حامد; يونس طويل (جامعة الوادي University Of Eloued, 2024)
"تهدف مذكرتنا إلى تقييم أداء الشبابيك (النوافذ ) الإسلامية في البنوك التقليدية بعد توجهها لإنشاء نوافذ إسلامية تابعة لها تهتم بتقديم خدمات ومنتجات إسلامية وقمنا بتتبع الإطار النظري لفكرة الشبابيك الإسلامية ودوافع ومتطلبات وضوابط تأسيسها . وقد استعملنا المنهج الوصفي التحليلي في دراستنا، اعتمادا على المعطيات النظرية من جهة والإحصائيات الواردة من البنك الوطني الجزائري وكالة بريكة من سنة 2021 إلى 2023 وتتبعنا القوانين ذات الصلة بالشبابيك الإسلامية ، مفسرين شروط فتح الحساب ومنتجات الشبابيك الإسلامية في البنك الوطني الجزائري وكيفية تسييرها بناء على التعليمات والشروط من بنك الجزائر. وتطبيقيا قيمت الدراسة النتائج المحققة على مستوى وكالة البنك الوطني الجزائري ببريكة من خلال نتائج فتح الحسابات . وخلصنا إلى أن تجربة فتح الشبابيك الإسلامية في البنوك العمومية التقليدية لقيت استحسانا من طرف الزبائن وتأسيسا من طرف كل البنوك العمومية لما حظيت به من تسهيلات من طرف النظام البنكي ككل وبنك الجزائر تحديدا النظام الجزائري بشكل خاص وعن وكالة البنك الوطني الجزائري ببريكة. " " Our note aims to evaluate the performance of Islamic windows in traditional banks after turning to the Islamic windows that are affiliated with them, which provide Islamic services and products, and we follow the framework of consideration of the idea of Islamic windows and their motives, requirements and necessities. We used descriptive analytical models in our study, relying on basic data in terms of statistics and reporting from the National Bank of Algeria and Barika Agency from the year 2021 to 2023. We followed the laws related to Islamic windows, explaining the conditions for opening Islamic accounts and subscriptions in the National Bank of Algeria and how to manage them based on the instructions and conditions. From the Bank of Algeria. In practice, the results of the study achieved at the level of the National Bank of Algeria agency in Barika were evaluated through the results of opening documents. We concluded that the experience of opening Islamic windows in traditional public banks was well received by customers and was established by all public banks due to the facilities they received from the banking system as a whole, the Bank of Algeria in particular, the Algerian system in particular, and the agency of the National Bank of Algeria in Brika. "
مذكرة ماستر
Keywords: الشبابيك الإسلامية – صيغ التمويل والادخار – البنك الوطني الجزائري – البنوك العمومية; Islamic windows - financing and saving formulas - National Bank of Algeria- public banks